Pengembangan Bank Sampah Sebagai Salah Satu Solusi Pengelolaan Sampah Anorganik Di Kelurahan Kandri Kecamatan Gunungpati - Carina Sarasati; Tri Susetyo Andadari; Taufiq Rizza Nuzuluddin; Maria Rosita Maharani; Adi Sasmito (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
To create a clean tourist village, the people of Kandri Village carry out waste management using the 3R system (reduce, reuse, recycle). This system takes the form of a waste bank that effectively manages inorganic waste while providing economic benefits for the surrounding community. One of the active waste banks in Kandri Village, Gunungpati District is the "Nuri" Waste Bank which is located at RT 09 RW 04. To develop inorganic waste management at this waste bank, it is necessary to socialize and build an inorganic waste storage space which is carried out in the form of 'Devotion' activities. to Society'. The method includes physical construction and socialization of inorganic waste management at the "Nuri" Waste Bank. The final result of this activity is the development of a physical building for storage space for segregated and weighted inorganic waste at the "Nuri" Waste Bank before it is collected by officers. Another result is the socialization of the management of the "Nuri" Waste Bank which is expected to increase community participation and provide environmental and economic benefits, especially for the people of Kandri Village, Gunungpati District.